Predominance of canine parvovirus 2b in Japan: an epidemiological study during 2014-2019 - Takano, Tomomi; Hamaguchi, Shun; Hasegawa, Nobuhisa; Doki, Tomoyoshi; Soma, Takehisa (Archives of virology, 2021)
Canine parvovirus 2 (CPV-2) is an important pathogen of domestic dogs and wild canids. In Japan, CPV-2 infection is one of the most common infectious diseases of dogs. We analyzed samples collected between 2014 and 2019 to identify antigenic variants of CPV-2 in dogs in Japan. Our results demonstrated that the CPV-2b variant was predominant. The CPV-2c variant was not found among our samples. Our findings demonstrate that the distribution of CPV-2 antigenic variants in Japan was more similar to that in Australia than to that in neighboring countries in Asia.